Low-noise time-resolved optical sensing of electromagnetic pulses from petawatt laser-matter interactions - Robinson,TS; Consoli,F; Giltrap,S; Eardley,S; Hicks,G; Ditter,E; Ettlinger,O; Stuart,N; Notley,M; De,Angelis R; Najmudin,Z; Smith,R (Scientific Reports, 2017)
We report on the development and deployment of an optical diagnostic for single-shot measurement of the electric-field components of electromagnetic pulses from high-intensity laser-matter interactions in a high-noise environment. The electro-optic Pockels effect in KDP crystals was used to measure transient electric fields using a geometry easily modifiable for magnetic field detection via Faraday rotation. Using dielectric sensors and an optical fibre-based readout ensures minimal field perturbations compared to conductive probes and greatly limits unwanted electrical pickup between probe and recording system. The device was tested at the Vulcan Petawatt facility with 1020 W cm−2 peak intensities, the first time such a diagnostic has been used in this regime. The probe crystals were located ~1.25 m from target and did not require direct view of the source plasma. The measured signals compare favourably with previously reported studies from Vulcan, in terms of the maximum measured intra-crystal field of 10.9 kV/m, signal duration and detected frequency content which was found to match the interaction chamber’s horizontal-plane fundamental harmonics of 76 and 101 MHz. Methods for improving the diagnostic for future use are also discussed in detail. Orthogonal optical probes offer a low-noise alternative for direct simultaneous measurement of each vector field component.